Malocclusion and orthodontic treatment need in Phu Mau and Vinh Ninh primary school children, Thua Thien Hue province - Nguyen, Ngoc Tam Dan; Ngo, Thi My Trinh; Hoang, Anh Dao (Tạp chí Y Dược Huế, 2022)
Malocclusion is a common dental health problem and can affect the health and life of people. The assessment of malocclusion helps to determine the need for orthodontic treatment according to the two components of dental health and dental aesthetics, which is very important to help improve the effectiveness of intervention and prevention methods necessary. Objectives: To determine the prevalence of malocclusion of primary school students, to determine the need for orthodontic treatment of primary school students according to the index of needs for orthodontic treatment, and the relationship with malocclusion. Method: A cross- sectional descriptive study on 220 primary school students aged 7 - 9 at two primary schools in Thua Thien Hue province from June 2021 to September 2021. Conduct oral examination, collect information, measure, observe and record indicators of malocclusion and orthodontic needs. Results: The results of the study on 220 students showed that the ratio of molars in the Angle I direction was the highest, accounting for 45%, and malocclusion was quited high (79.09%). Regarding the need for orthodontic treatment, according to DHC- IOTN, 39.55% had little treatment and according to AC-IOTN, 36.6% had moderate treatment. There is a strong correlation between malocclusion status and DHC-IOTN (r=0.65, p>0.05), malocclusion and AC-IOTN have an average correlation (r=0.44, p>0.05). There is also a strong correlation between AC-IOTN and DHC-IOTN (r=0.60, p>0.05). There was no gender difference between treatment levels for dental health and dental aesthetics with p>0.05. Conclusions: malocclusion in 7-9 years old students is quited high - the need for orthodontic treatment according to both dental health components, and aesthetics dentistry. It is necessary to provide timely and effective interventions to improve the oral health of children.